Analysis on the virulomes and resistomes of multi-drug resistance clinical Escherichia coli isolates, as well as the interactome with gut microbiome. (November 2020) - Chen, Ding-Qiang; Huang, Tengyi; Wang, Qun; Bai, Caiying; Yang, Ling
Abstract: Escherichia coli is one of the most diverse microbial species. Pathogenic E. coli is capable of causing various diseases in humans, including several types of diarrhea, urinary tract infections, sepsis, and meningitis. This study focused on the antibiotic susceptibility profile and genomic analysis of a clinical E. coli Guangzhou-Eco330 isolated from a hospitalized 8-year-old female patient suffered from pulmonary infection in 2017. Susceptibility to 15 antibiotics were determined using Vitek2™ Automated Susceptibility System and Etest strips and interpreted based on CLSI guidelines. The genome was sequenced using Illumina Hiseq 2500 platform and assembled de novo using Velvet, followed by bioinformatics analysis. The genome has a length of 5, 132, 642 bp and contains 4989 predicted genes with an average GC content of 50.51%. The carriage of rfbE gene suggested the strain belonging to O157. In the genome, 70 non-coding RNAs, 50 repeat sequences, 18 transposons, 78 GIs, 9 CRISPRs, and 3 large prophages were identified. 37 PHI related genes and 108 virulence genes were determined to contribute to its pathogenicity. Specifically, the acquisition of multiple antibiotic resistance genes including bla CTX-M-55, bla OXA-10, bla CMY-48, tetB, and qnrS1 contributed to its resistance to penicillins, telracyclines, cephalosporin, and quinolones. The understanding of the genome may aid in further study on the clinical control of multi-drug resistance E. coli . Highlights: The acquisition of multiple resistance genes contributed to resistance to penicillins, telracyclines, cephalosporin, and quinolones. The presence of multiple virulence factors was important for bacterial pathogenesis. The understanding of the genome may aid in further study on the clinical control of MDR  E. coli .